Heavy metal transport driven by seawater-freshwater interface dynamics: The role of colloid mobilization and aquifer pore structure change. (15th June 2022) - Tan, Bo; Liu, Chao; Tan, Xiao; You, Xueji; Dai, Chaomeng; Liu, Shuguang; Li, Jun; Li, Naiwen
Highlights: Substantial colloid-bonded metals liberate behind the seawater interface propagation. Interface dynamics drives colloidal repulsive energy barrier to enhance. Mobile colloids provide a privileged transit pathway for the adsorbed heavy metals. Aquifer pore structure evolution links the size-selective transport of colloids. Abstract: Co-transport of colloidal substances and pollutants is a pivotal link that significantly affects the environment of coastal groundwater. The effect of colloid mobilization and aquifer pore structure change on heavy metal transport driven by seawater-freshwater interface dynamics is not fully understood. In this study, packed column experiments were conducted to model the seawater intrusion (SWI) and freshwater replenishment (FWR) processes using a sampled medium from a coastal sandy aquifer. Hydrodynamic, hydrochemical variables, and heavy metal (Pb, Cu, Cd) transport during the propagation of the seawater-freshwater interface were tested and analyzed. During the SWI stage, cation exchange induced heavy metal liberations, and it developed peak concentrations synchronized with the seawater-freshwater interface at the pore volume of 1.00. The colloid-facilitated transport for heavy metals was the predominant mechanism in the FWR stage, characterized by a peak release lagging the interface propagation by approximately 0.5 pore volumes. Because the colloidal fraction was mobilized during aquifer desalination, it lagged behind the decline of the salinity gradient. Furthermore, Derjaguin-Landau-Verwey-Overbeek (DLVO) calculations explained that the replenishment decreased the depth of the secondary energy minimum of the colloids; meanwhile, the thickness of the electrical double layer increased from 0.63 nm to 10.14 nm, resulting in a repulsive energy barrier up to 3, 213 kT. The transport of colloids led to a reduction in porosity from 18.16% to 2.28% of the total immobile domain. At these times, the dimension of the transported colloids evolved, showing a size-selective transport and therefore regulating the total emission fluxes of the heavy metals. These mechanisms were proposed to be incorporated in colloid filtration theory for targeting the coastal scenario. Graphical abstract: Image, graphical abstract